Biomarkers of cadmium, lead and mercury exposure in relation with early biomarkers of renal dysfunction and diabetes: Results from a pilot study among aging Canadians. (15th September 2019) - Valcke, Mathieu; Ouellet, Nathalie; Dubé, Marjolaine; Laouan Sidi, Elhadji A.; LeBlanc, Alain; Normandin, Louise; Balion, Cynthia; Ayotte, Pierre
Highlights: Cd, Pb and Hg levels were measured in urine and blood from 70 aging canadians. Metabolomic profiles were determined for T2D-related branched chain amino acids. Biomarkers of early renal dysfunction and risk of T2D were also measured. Linear and structural equation models were performed between measured biomarkers. Results suggest relations between urinary Cd or Hg, with KIM or RBP and adiponectin. Abstract: Cadmium (Cd), lead (Pb) and mercury (Hg) are known nephrotoxicants that have been associated with the risk of developing type-2 diabetes (T2D). The aim of this pilot study was to explore relations between biomarkers of Cd, Pb and Hg exposure, early urinary biomarkers of renal dysfunction (kidney-injured molecule-1 (KIM-1), N-acetylglucosaminidase and retinol-binding protein (RBP)) and plasma biomarkers deemed predictive of the risk of developing T2D (adiponectin, leptin, branched-chain and aromatic amino acids), among 70 participants (age range: (46–87 yrs)) from the Canadian Longitudinal Study on Aging (CLSA) with normal glycemic control (glycated haemoglobin ≤ 6.5%) in all but four of them. Significant (p < 0.05) Spearman correlation coefficients were obtained between: plasma adiponectin and RBP (r = 0.42), urinary Cd (r = 0.32), blood Cd (r = 0.36); KIM-1 and CdU (r = 0.33) as well as HgU (r = 0.37); RBP and isoleucine (r = -0.28), leucine (r = -0.33), tyrosine (r = -0.3) and valine (r = -0.44); CdU and isoleucine and valine (r = -0.27 for both). Multiple linear regression analyses showed that some T2D-related biomarkers are confounders of associations between RBP and Hg or Cd biomarkers. Path analyses support a mediating effect of adiponectin on the relation between urinary Cd and RBP. Concluding, this pilot study originally investigated a comprehensive set of biomarkers on complex interactions between toxic metal exposure, renal function and T2D in a group of aging Canadians. Its findings warrant further investigation of longitudinal data in a greater number of participants.